TRADE LIBERALIZATION AND CONSUMER VULNERABILITY: A LEGAL FRAMEWORK ON LEGISLATIONS AND TESTING MECHANISM FOR ASEAN PRODUCT SAFETY DIRECTIVE - Syed Sagoff Alsagoff; Rahmah Ismail (Faculty of Law, Sriwijaya University, Indonesia, 2017)
Since its inception in 1967 ASEAN has advanced in great leaps in the economic sector luring new member states into its pact. From a mere five member states (Malaysia, Indonesia, Thailand, Singapore and the Philippines) ASEAN has today managed to entice five other neighbouring states (Brunei 1984, Vietnam 1995, Laos & Myanmar 1997, Cambodia 1999) into its pact transforming itself into union of ten member states with a consumer population expected to exceed 600 million people. In order to ensure sustainability amid global challenges, member states have engrossed ASEAN Charter in 2007 with a view of creating an ASEAN Economic Community by 2015 that is robust, competitive and sustainable. At this juncture, ASEAN has to realize that like any trade liberalization initiatives, goods moved readily and freely throughout the free-trade area that is facilitated by a lucrative non-barrier tariffs incentives. This vision of a single market which creates a frontier without borders can prove to be advantageous to member states only if they have the required vehicle that is able to overcome the drawback of its progression through harmonization and synchronization efforts that is effective and successful. Like everything else, every advantage has some disadvantages attached to it. This article will address important determining factors that are crucial in the development and scope of proposed ASEAN Product Safety Directive including reviewing relevant determining factors such as regional stability, consumer protection legislations and standard and testing agencies of which one without the other will be incomplete. The proposals suggested in this article will strengthen and unite ASEAN in overcoming unsafe product issues at ASEAN level.